(untitled) (Research, Society and Development, 2021)
The objective of this study was to evaluate the daily maxillary and tibial bone mineral apposition rate of ovariectomized rats and orchiectomized rats through confocal laser microscopy. Twenty-four animals were divided into 4 groups (SHAMF, OVX, SHAMM and ORQ). Six rats were distributed to the SHAMF group (submitted to fictitious surgery); six rats to the OVX group (submitted to bilateral ovariectomy); six rats to the SHAMM group (submitted to fictitious surgery) and six rats to the ORQ group (submitted to bilateral orchiectomy). On the 60th day after the surgical procedures the animals received 20 mg/kg of calcein and after 24 days 20 mg/kg of alizarin red was administered. The euthanasia was performed 18 days after the last fluorochrome administration. The histological slides obtained were submitted to confocal microscopy analysis and then dynamic histomorphometry was performed to obtain the daily mineral apposition rate (MAR). In the tibias, the values of MAR were higher for the SHAMF group (P<0.05) (mean: 37.1μm² / day) compared to the ORQ group (mean: 7.16 μm²). In the jaws, the values were higher for the SHAMF group (P<0.05) (mean: 5.175μm² / day) compared to the SHAMM group (mean: 1.84 μm²), OVX (mean: 3.027 μm²) and ORQ group (mean: 1.56 μm²). It can be concluded that the female gender, regarding the characteristics of the maxillary and tibial bones, presented a daily mineral bone apposition rate higher than the male gender, mainly in the maxillary bone, presenting a statistically significant difference between all groups studied.